All Days 2011
DOI: 10.2118/141091-ms
|View full text |Cite
|
Sign up to set email alerts
|

Single-well In-situ Measure of Oil Saturation Remaining in Carbonate after an EOR Chemical Flood

Abstract: The MicroPilot* is a log-drill-inject-log sequence of operations designed to evaluate the improvement in oil recovery resulting from the addition of chemicals to the injected water. The fluid to be injected is transported downhole in a sample chamber and injected into the formation through a pencil sized drilled hole, with measurements of the resulting changes in saturation proximal to the well. This technique was first used during 2009 in Oman to perform an in-situ test of alkaline surfactant polymer in high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…There are several methodologies available to estimate ROS/Sor from logs (Al-Harbi, 2011; Schmitt, 2011) from a single pass, including Resistivity, NMR, PNL (Pulsed Neutron logs, C/O and Sigma) and dielectric logs; or from multiple passes, including NMR LILfor shortening or "killing" the water signal by doping the mud (Horkowits, J.P., 1997;Hassoun, T.H., 1997), and Micro injectivity pilot for in-situ injection with a Wireline Formation Tester (Arora, 2010;Edwards, 2011). In the case of the gas cap in Mauddud there is an additional complication, because three fluid phases co-exist in the reservoir: gas, oil and water.…”
Section: Saturation From Logsmentioning
confidence: 99%
“…There are several methodologies available to estimate ROS/Sor from logs (Al-Harbi, 2011; Schmitt, 2011) from a single pass, including Resistivity, NMR, PNL (Pulsed Neutron logs, C/O and Sigma) and dielectric logs; or from multiple passes, including NMR LILfor shortening or "killing" the water signal by doping the mud (Horkowits, J.P., 1997;Hassoun, T.H., 1997), and Micro injectivity pilot for in-situ injection with a Wireline Formation Tester (Arora, 2010;Edwards, 2011). In the case of the gas cap in Mauddud there is an additional complication, because three fluid phases co-exist in the reservoir: gas, oil and water.…”
Section: Saturation From Logsmentioning
confidence: 99%
“…Cherukupalli et al (2010) presented flow modeling of the first MicroPilot showing that the saturation changes measured by the logs could be successfully matched by a relatively simple model of the ASP process. Finally, Edwards et al (2011) recently reported on the second application of the technique, which was conducted in a light-oil carbonate reservoir using an alkaline-surfactant mixture as EOR fluid.…”
Section: Introductionmentioning
confidence: 99%